KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA SMP DI KABUPATEN KARAWANG PADA MATERI BANGUN DATAR - Diki Laksono; Kiki Nia Sania Effendi (IKIP Siliwangi, 2021)
This study aims to determine the actual situation of student with indicators of mathematical creative thinking abilities used are originality, fluency, elaboration and flexibility to determine their mathematical creative thinking skills. Creative thinking is defined as the basic abilities that must be mastered and developed by each student with the aim of creating new things, new ways or giving new idea in generating ways to produce new ways and solve problem as alternative solutions that are different from those that already exist before. A total of 37 student of class 8 at one of the state junior high schools in Karawang regency were the research subject and qualitative descriptive as the research method. There are 4 questions about the ability to think mathematically creatively on the flat shape material as a tes instrument given to student. Data analysis in this research is data reduction, data display, and verification. The results of this study were the lowest score 18,75 and highest score of 93,75with an average score of 35,3. The conclusion is that students’ mathematical creative thinking skills in junior high school students in karawang city are less creative.